2018
DOI: 10.1128/aem.00507-18
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Leptospira interrogans Survival in Soil and Water Microcosms

Abstract: is the etiological agent of leptospirosis, a globally distributed zoonotic disease. Human infection usually occurs through skin exposure with water and soil contaminated with the urine of chronically infected animals. In this study, we aimed to quantitatively characterize the survival of serovar Copenhageni in environmental matrices. We constructed laboratory microcosms to simulate natural conditions and determined the persistence of DNA markers in soil, mud, spring water and sewage using a quantitative PCR (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
3
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 45 publications
(50 reference statements)
5
97
3
7
Order By: Relevance
“…The 1 to 2 weeks lag between rainfall, temperature, or humidity and leptospirosis identified here, as well as the 2 weeks lag between rainfall and flooding reported in Manila, contrast with results from previous studies that used monthly data and suggested longer temporal association between onset of symptoms of leptospirosis and meteorological data (2 to 10month lags respectively) [18][19][20]46]. Therefore, though leptospires survive for up to one year and remain virulent in culture conditions that mimic the external environment in vitro [45,47,48], L. interrogans survival in spring water decreases to 3 weeks [49].…”
Section: Discussioncontrasting
confidence: 82%
“…The 1 to 2 weeks lag between rainfall, temperature, or humidity and leptospirosis identified here, as well as the 2 weeks lag between rainfall and flooding reported in Manila, contrast with results from previous studies that used monthly data and suggested longer temporal association between onset of symptoms of leptospirosis and meteorological data (2 to 10month lags respectively) [18][19][20]46]. Therefore, though leptospires survive for up to one year and remain virulent in culture conditions that mimic the external environment in vitro [45,47,48], L. interrogans survival in spring water decreases to 3 weeks [49].…”
Section: Discussioncontrasting
confidence: 82%
“…A broad range of mammalian reservoirs harbor the spirochete in their renal tubules shedding the bacteria in their urine for long periods of time 6,7 . Leptospirosis is an environmentally-transmitted disease, for which the primary mode of transmission to humans is through contact with contaminated water or soil 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Human leptospirosis in Salvador appears to be solely caused by L. interrogans serogroup Icterohaemorrhagiae. Such pathogenic leptospires are not known to reproduce in the environment, and survival at least of the vast majority of the population is short (Evangelista and Coburn, 2011;Casanovas-Massanaa et al, 2018). Therefore, reduction in the rodent population will, in turn, reduce the environmental load of leptospires.…”
Section: Introductionmentioning
confidence: 99%